English-majored Students’ Self-directed Learning Strategies for taking English Certificates in the fulfillment of Program Outcome Standards - Nguyen, Thuong; Tran Manh, Dai (EDUPEDIA Publisher, 2026)
Purpose – This study investigates English-majored students’ perceptions of self-directed learning (SDL) strategies used to prepare for English certification exams within Vietnam’s credit-based higher education system, which requires increased learner autonomy. It aims to determine the extent of SDL engagement and identify factors influencing the effectiveness of these strategies. Methodology – A mixed-method design was employed. Quantitative data were collected through a structured questionnaire administered to English-major students (sample size not specified), followed by qualitative data from semi-structured interviews with selected participants. The instruments examined SDL behaviors, frequency of strategy use, motivation, and challenges. Data were analyzed using descriptive statistics for survey responses and thematic analysis for interview data. Findings – Results indicate varied levels of SDL engagement. Approximately half of the students reported actively applying SDL strategies, while many used them only occasionally, reflecting uneven commitment to certification preparation inside and outside the classroom. Key factors affecting effectiveness include motivation, use of appropriate learning strategies, and procrastination. Interview findings highlight the need for improved self-regulation skills, stronger student–teacher and peer interactions, and greater institutional and external support. These findings suggest that enhancing structured guidance and support systems can improve SDL outcomes and certification success. Novelty – The study contributes empirical evidence on SDL practices specific to English certification preparation within Vietnam’s credit-based system, integrating both quantitative trends and qualitative insights. Significance – The findings benefit language educators, curriculum designers, university administrators, and students by informing policies and pedagogical approaches that foster effective autonomous learning.